FORMAL EDUCATION LEAVES WOMEN FROM THE TRIBUTES OF CHILDHOODS IN SOUTH KALIMANTAN: (Analysis of Demographic and Health Data of Indonesia Year 2012) - Norma Yuni Kartika (Department of Geography Education, University of Jember, 2018)
Education is